Análisis de sistemas de aprovechamiento de residuos orgánicos mediante la utilización de la mosca soldado negra (Hermetiaillucens). (2022)
The black soldier fly (Hermetia illucens sp.) contributes exponentially to sustainable agriculture because it is efficient in reducing the volume of organic waste, while at the same time converting it into protein-rich biomass. the administration of organic waste in sanitary landfills is not enough to carry out adequate management in order to reduce the size of solid waste that reaches sanitary landfills. In Bogotá, 53.22% of the waste that reaches the landfills corresponds to organic waste according to the Special Administrative Unit of Public Services -UAESP (2014), of which no management is carried out; Because of this situation, alternatives are sought, such as the use of black soldier fly larvae, since they have the potential to be used as a biotechnological treatment in the management and use of organic waste from the agricultural and livestock sector, it is a kind of high performance to treat organic waste compared to other techniques due to its low cost and low maintenance.